Transcriptomic Analyses Reveal the Protective Immune Regulation of Conjugated Linoleic Acids in Sheep Ruminal Epithelial Cells - Yang, Chunlei; Lan, Wei; Ye, Shijie; Zhu, Binna; Fu, Zhengwei (Frontiers in Physiology, 2020)
The ruminal epithelium is continuously challenged by antigens released by the lysis of dead microbial cells within the rumen. However, the innate immune system of the ruminal epithelium can almost always actively respond to these challenges. The cross talk between the ruminal microbiota and innate immune cells in the ruminal epithelium has been suggested to play an important role in sustaining the balance of immune tolerance and inflammatory response in the rumen. We hypothesized that conjugated linoleic acid (CLA), a functional microbial metabolite in the rumen, may contribute to the immune regulation in rumen epithelial cells (RECs); therefore, we ﬁrst established an immortal REC line and then investigated the regulatory effects of CLA on the immune responses in these RECs. The results showed that long-term REC cultures were successfully established via SV40T-induced immortalization. Transcriptome analysis showed that a 100 μM CLA mixture consisting of 50:50 cis-9, trans-11:trans-10, cis-12 CLA significantly downregulated the expression of the inflammatory response-related genes TNF-α, IL-6, CX3CL1, IRF1, ICAM1 and EDN1, and upregulated the expression of the cell proliferation-related genes FGF7, FGF21, EREG, AREG and HBEGF and the lipid metabolism-related genes PLIN2, CPT1A, ANGPTL4, ABHD5 and SREBF1 in the RECs upon LPS stimulation. Correspondingly, the GO terms regulation of cell adhesion, response to stimulus and cytokine production and KEGG pathways TNF and HIF-1 signaling, ECM-receptor interaction and cell adhesion molecules were identified for the significantly downregulated genes, while the GO terms epithelial cell proliferation and regulation of epithelial cell migration and the KEGG pathways PPAR, ErbB and adipocytokine signaling were identified for the RECs with significantly upregulated CLA-pretreated genes upon LPS stimulation. These findings revealed that CLA conferred protective immunity onto the RECs by inhibiting proinflammatory processes, promoting cell proliferation and regulating lipid metabolism related to the immune response.